Analisis Faktor yang Mempengaruhi Minat Beli pada Marketplace Online di Kota Batam - Novitasari, Indah; Cuandra, Fendy (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the factors that influence consumer purchase intention in the online marketplace in Batam City. The independent variables proposed in this study include trust, convenience, customer service, hedonic motives, and usefulness motive, which are mediated by the attitude towards online shopping and moderated by trust in website. The research methodology used is quantitative. The data used is primary data from the results of a survey using an online questionnaire with 300 respondents. The analytical method used is the Structural Equation Model method using SmartPLS 3 software. The results of this study found that trust and convenience did not have a significant positive effect on attitudes toward online shopping. Consumer service, hedonic motives, and usefulness motives have a significant positive influence on attitude toward online shopping. Attitude toward online shopping affects purchase intention. Trust in website does not provide a moderating effect between attitudes toward online shopping and purchase intention. From the results of our research, it can be seen that consumer service, hedonic motives, and usefulness motives have a role in shaping consumer attitudes toward online shopping. Then the attitude will determine the purchase intention for products sold in online marketplaces.